Survei Kondisi Sarana dan Prasarana Tenis Meja dalam Mendukung Pembelajaran PJOK di SMP Katolik Tri Sakti II Medan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the condition and level of suitability of table tennis facilities and infrastructure in supporting Physical Education, Sports, and Health (PJOK) learning at Tri Sakti 2 Catholic Junior High School, Medan. The study used a descriptive method with an observational survey approach. Data were collected through direct observation, interviews with PJOK teachers and students, and documentation. Then, they were analyzed using descriptive analysis techniques by comparing the condition of the available facilities and infrastructure with the standards for the suitability of sports facilities at the school. The results showed that the table tennis facilities owned by the school were generally in a condition suitable for use, consisting of three table tennis tables, seven balls, five bats, two sets of nets and poles, one scoreboard, and one whistle, most of which were in good condition. Although one table had minor damage to the legs, the facility was still usable after simple repairs. However, from the infrastructure aspect, the school does not yet have a dedicated table tennis room so learning is still carried out on the multifunctional volleyball court. This finding indicates that the availability of facilities has supported PJOK learning, but limited infrastructure still hinders the optimization of practical activities, so that the development of facilities and the provision of a dedicated table tennis room are needed to improve the effectiveness of learning.